2020
DOI: 10.18805/ag.d-5140
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Mobile Apps used in India: Current Status and Gap Analysis

Abstract: Background: Agriculture plays a significant role in economic and social development in India. With the rapid development of Information and Communication Technologies, information and data can be effectively generated, stored and used by farmers to improve agricultural productivity. For this, smart farming technologies using mobile applications (apps) that help reduce costs, maximize yields and increase profits are being employed. Here, we present an overview of several mobile apps available for traceability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…On the other hand, a large number of mobile apps have been launched as a part of agro-solutions. In this regard, Balkrishna et al (2021) evaluated 73 agriculture mobile apps, which are used in different agriculture allied sectors. They found that out of these 73 apps, there are about 14% of apps are pertaining to pure agriculture, while 12% for farm management including geotagging.…”
Section: Government Initiativesmentioning
confidence: 99%
“…On the other hand, a large number of mobile apps have been launched as a part of agro-solutions. In this regard, Balkrishna et al (2021) evaluated 73 agriculture mobile apps, which are used in different agriculture allied sectors. They found that out of these 73 apps, there are about 14% of apps are pertaining to pure agriculture, while 12% for farm management including geotagging.…”
Section: Government Initiativesmentioning
confidence: 99%
“…The role of IoT has increased for auto pumping and to send information wirelessly (Vanaja et al 2018, Vijayakumar andRosario 2011). Around 73 mobile applications are used by the Indian farmers in various agricultural sectors (viz Farm management, livestock, animal husbandry etc) (Balkrishna et al, 2021). IoT devices can exchange data with other connected devices and application or collect data from other devices and process the data either locally or send the data to centralized servers or cloud-based applications backend for processing the data (Ray 2017).…”
Section: Introductionmentioning
confidence: 99%